DETERMINATION OF THE TECHNICAL (GEOMATRICAL) DEVIATIONS EXPRESING IN PLÜCKER COORDINATES FOR 4R SYMMETRICAL SPHERICAL QUADRILATERAL MECHANISM - Ion BULAC (Fiabilitate şi Durabilitate)
The technological (geometrical) deviations determine in the intermediate couples of the mechanism supplementary efforts due to restrained movement. The 4R asymmetrical spherical quadrilateral mechanism is multiple statically indeterminate, and for calculating the reactions from the kinematic pairs it is applied the elastic linear calculation using the relative displacements method. The equations of elastic balanced are written in the general system of reference.For this is necessary the knowledge the forms of the technical (geometrical) deviations in the general system of reference.This paper presents the calculation modality these deviations .